Galperian epistemology, human thought, and artificial intelligence in education - Querubín Patricio Flores Núñez; Tiago Felipe Vera-Assaoka; Juan Carlos Huircalaf Diez (International Journal of Evaluation and Research in Education (IJERE), 2026)
This theoretical review examines the relationship between Piotr Galperin’s epistemology, the development of human thought, and the incorporation of artificial intelligence (AI) in education. The analysis is organized around five issues: the stage-by-stage formation of mental actions, the zone of proximal development as oriented mediation, the pedagogical role of AI, the ethical and cultural risks of automation, and practical principles for educational design and regulation. The review synthesizes contributions from historical-cultural psychology, activity theory, neuroeducation, ethics of technology, and recent AI-in-education studies in order to argue that AI should not be understood as a substitute for human thinking but as a mediated resource whose value depends on pedagogical intentionality, transparency, and cultural grounding. The paper’s explicit novelty lies in articulating Galperin’s orienting basis of action with current debates on AI design, educational policy, and ethical regulation, thereby moving from philosophical interpretation to concrete pedagogical criteria for practice. From this perspective, the teacher remains a reflective mediator, and education retains its formative responsibility to cultivate autonomy, critical judgment, and consciously regulated action.